INFORMATION SECURITY POLICY UPDATES AND INFORMATION SECURITY BREACH INCIDENTS OF SACCOS IN KENYA - Sirma, Jerotich; Raburu, George; Okelo, N. B (IJRDO -Journal of Computer Science Engineering, 2015)
The study analyzed the Impact of Information Security Policies on security breach incidences in Kenyan Savings and Credit Cooperatives Societies (SACCOS). Information is an important organizational asset that that is mainly vulnerable to attacks from user error, hackers and crackers, viruses and cyber criminals. This has resulted in loss of trillions of dollars around the world and over 4 billion shillings in East Africa. The study investigated whether information security policies assist in preventing unauthorized individuals from accessing SACCOS’ sensitive information. The study looked at the relationship between dependent and independent variables. The dependent variable was incidences of security breaches while the independent variables were investigation of the relationship between information security policy updates (frequency) and information security breach incidents. The results of the study revealed that there is a weak relationship between information security policies and security breach incidences in the SACCOS sector. The study results hope to add to the body of academic knowledge and practitioners in the SACCOS sector where information repository is a resource.